2010
DOI: 10.1002/elan.200900401
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Controlled Release System for Risperidone Using Polypyrrole: Mechanistic Studies

Abstract: Polypyrrole (PPY) film has been selected as a platform material for drug delivery due to its inherent conductivity, ease of preparation and apparent biocompatibility. PPY films were prepared containing the antipsychotic drug risperidone as a model compound. Drug release profiles could be altered by applying different electrical stimulation to these films. Atomic force microscopy was used to investigate changes in PPY film thickness when different stimuli were applied. The highest levels of drug release were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 25 publications
(29 reference statements)
1
21
0
1
Order By: Relevance
“…A parametric study, implementing different CV‐ranges, unraveled that release triggering is not solely based on the elimination of the electrostatical binding of the dopant to the polymer. Moreover, the mechanical actuation of the polymer contributes significantly to the release of the drug and the monomer as has been described by others for different drugs . The EDOT could be shown to originate from the polymer bulk.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…A parametric study, implementing different CV‐ranges, unraveled that release triggering is not solely based on the elimination of the electrostatical binding of the dopant to the polymer. Moreover, the mechanical actuation of the polymer contributes significantly to the release of the drug and the monomer as has been described by others for different drugs . The EDOT could be shown to originate from the polymer bulk.…”
Section: Resultsmentioning
confidence: 63%
“…However, there is also a considerable release of both Dex and EDOT in the anodic sweep, which indicates that not only the electrostatical mechanism but also the swelling and deswelling of the film during actuation contribute significantly to the drug release. Studies by Svirskis et al showed the successful release of cationic (risperidone) as well as neutral (progesterone) substances during electrical activation of a PPy film, which demonstrates the substantial effect of mechanical film actuation on the expulsion of charged and uncharged molecules. This mechanical release mechanism is further believed to dominate the active EDOT release from our samples as no clear suppression can be seen in any of the sweep ranges, which would be expected for a direct correlation to the sweeping potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, small molecule drugs such as, glutamate, 13 dexamethasone, 14 risperdone, 15 etc. can be released from conducting polymer thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Os PCs têm sido estudados em diversas aplicações tecnológicas: músculos artificiais [51][52][53][54], sistemas inteligentes de liberação controlada [7,[55][56][57][58][59], engenharia de tecido [60][61][62][63][64], biosensores [65][66][67], neurônios artificiais [68][69][70][71][72], supercapacitores [73][74][75][76][77][78] …”
Section: Aplicações Dos Pcsunclassified